Case report: TP53 and RB1 loss may facilitate the transformation from lung adenocarcinoma to small cell lung cancer by expressing neuroendocrine markers - Li, Jun; Wei, Bing; Feng, Junnan; Wu, Xinxin; Chang, Yuxi; Wang, Yi; Yang, Xiuli; Zhang, Haiyan; Han, Sile; Zhang, Cuiyun; Zheng, Jiawen; Groen, Harry J. M.; et al. (Frontiers in Endocrinology, 2022)
Transformation from lung adenocarcinoma (LUAD) to small cell lung cancer (SCLC) is one of the mechanisms responsible for acquired EGFR-TKIs resistance. Although it rarely happens this event determines a rapid disease deterioration and needs specific treatment. Here, we report a case of 75-year-old LUAD female with a p.L858R mutation in Epidermal Growth Factor Receptor (EGFR) who presented with SCLC transformation after responding to first line osimertinib treatment for only 6 months. By retrospectively analyzing the first (LUAD) and the second (SCLC) biopsy, we found mutations in EGFR p.E709A and p.L858R, Tumor Protein p53 (TP53) p.A159D and Retinoblastoma 1 (RB1) c.365-1G>A in the diagnostic LUAD and in the transformed SCLC sample. In addition to these mutations, we also observed a high copy number gain for Proto-Oncogene C-Myc (MYC) and a Phosphoinositide 3-Kinase Alpha (PIK3CA) p.E545K mutation, which were specific for the transformed sample. We consider the combined presence of the MYC amplification with the mutations in TP53 and RB1 as drivers of the transformation to SCLC. Our results highlight the need to systematically evaluate TP53 and RB1 status in LUAD patients to offer a different therapeutic strategy.